A Class of Univalent Functions with Negative Coefficients defined by Hadamard Product with Komatu Integral Operator - Shanmugam, T. N.; Ramachandran, C.; Prabhu, R. Ambrose (Communications in Mathematics and Applications, 2013)
In our paper, we study a class SRA(λ, β, α, μ, θ) which consists of analytic and univalent functions with negative coefficients in the open unit disk U={z:| z | < 1 } defined by Hadamard product (or convolution) with Komatu integral operator, we obtain coefficient bounds and exterior points for this class. Also Distortion Theorem using Fractional Calculus techniques and some results for this class are obtained.